Astaxanthin increases progesterone production in cultured bovine luteal cells - KAMADA, Hachiro (J Vet Med Sci, 2017)
Although astaxanthin (AST) is known to be a strong antioxidant, its effects on reproductive function in domestic animals have not yet been elucidated in detail. Therefore, we investigated the effects of AST on luteal cells, which produce progesterone (P4), an important hormone for maintaining pregnancy. Luteal cells were prepared by collagenase dispersion of the corpus luteum (CL). The addition of racemic AST at a low concentration (<10 nM) to cultured bovine luteal cells increased P4 in the culture medium (P<0.05). This effect was attributed to an increase in the ability of luteal cells to produce P4 (P4/cell·DNA); however, the level of lipid peroxide (TBARS: thiobarbituric acid reactive substances) per cell did not decrease with the addition of AST, whose values were similar to that with the addition of luteinizing hormone. When optical isomers of AST (SS and RR types) were added to the culture medium, respectively, SS-AST was more effective in increasing P4 production than RR-AST. When 1 mg/kg·body weight of SS-AST derived from green algae was fed to cows for 2 weeks, its concentration in blood plasma was 10.9 nM on average, which was sufficient to expect an in vitro effect on the production of P4 in cows. These results suggested the potential of SS-AST supplements for cows to elevate luteal function.